Survival estimates for elite male and female Olympic athletes and tennis championship competitors - Coate, D.; Sun, R. (Scandinavian Journal of Medicine & Science in Sports, 2013)
In this paper, we report survival estimates for male and female Olympic medal winners and for male and female finalists at the British and U S national tennis championships. We find a consistent longevity advantage of Olympic medal-winning female athletes over Olympic medal-winning male athletes competing separately in the same events since 1900 and for female finalists over male finalists competing separately in the finals of the national tennis championships of Britain and of the United States since the 1880s. This is the case for sample mean comparisons, for Kaplan-Meier survival function estimates, including life expectancy, and for Cox proportional hazard estimates, which show statistically significant lower hazard rates for women with birth year and other variables constant. The female longevity advantage over males is similar in the early period samples (birth years before1920) and in the full period samples, and is 5-7 years.